An improvement of Energy Efficient Multipath Routing Node Management Techniques for MANET - Rajeshkanna, R.; Saradha, DrA. (IJRDO -Journal of Computer Science Engineering, 2016)
A mobile ad hoc network (MANET) is a continuously self-configuring, infrastructure-lessnetwork of mobile devices connected wirelessly. Each device in a MANET is free to moveindependently in any direction, and will therefore change its links to other devices frequently. In suchnetworks, the mobile nodes may dynamically enter the network as well as leave the network. Due to therestricted transmission range of wireless network devices, multiple hops are usually needed for a node toexchange information with any other node in the network. A joint routing and energy allocation plan isdeveloped which stabilizes the system and provides surrounded average delay guarantees whenever theinput rates are within this capacity segment. This paper considers jointly optimal design of cross layercongestion control, routing overhead and Throughput for Mobile ad hoc networks